Electrochemical Degradation of the Antihypertensive Losartan in Aqueous Medium by Electro-Oxidation with Boron-Doped Diamond Electrode - Salazar-Gonzalez, R (Elsevier B.V., 2016)
In this work the electrochemical oxidation of losartan, an emerging pharmaceutical pollutant, was studied. Electrochemical oxidation was carried out in batch mode, in an open and undivided cell of 100 cm3 using a boron-doped diamond (BDD)/stainless steel system. With Cl− medium 56% of mineralization was registered, while with the trials containing SO42− as supporting electrolyte a higher mineralization yield of 67% was reached, even obtaining a total removal of losartan potassium at 80 mA cm−2 and 180 min of reaction time at pH 7.0. Higher losartan potassium concentrations enhanced the mineralization degree and the efficiency of the electrochemical oxidation process. During the mineralization up to 4 aromatic intermediates were identified by ultra high performance liquid chromatography tandem mass spectrometry (UHPLC–MS/MS). Moreover, short-linear carboxylic acids, like oxalic, succinic and oxamic were detected and quantified by ion-exclusion HPLC. Finally, the ability of the electrochemical oxidation process to mineralize dissolved commercial tablets containing losartan was achieved, obtaining TOC removal up to 71% under optimized conditions (10 mA cm−2, 0.05 M Na2SO4, pH 7.0 and 25 °C and 360 min of electrolysis). © 2016 Elsevier B.V.